Structural performance of one-way slabs reinforced with steel and polypropylene fibers - uz Zaman Khan, Qaiser; Ahmad, Afaq; Raza, Ali; Labibzadeh, Mojtaba; Iqbal, Muhammad (Penerbit Universiti Kebangsaan Malaysia, 2021)
The present study aims to investigate the effects of the steel fibers (SF) and polypropylene fibers (PPF) on the structural response of one-way simply supported reinforced concrete (RC) slabs at the ultimate limit state (ULS). Next, an optimized combination of the hybrid fibers is proposed. The experimental program includes 21 experiments on the one-way slabs with different SF and PPF ratios. The load-deflection curves were obtained for slabs using a four-point bending method. The ultimate capacity and mid-span deflection of the slabs were measured. The experimental results did not produce a consistent trend of ultimate loading. The different blends produced different failure modes, cracking load, and ultimate failure load. Based on the obtained test results, the slab specimen, SM6, with 0.7% SF and 0.9% PPF ratios has the maximum and the slab specimen, SM16, with 0.9% SF and 0.9% PPF ratios has the minimum load-carrying capacity, respectively. The first shows a 31% increase and the second indicates a 31% reduction when compared to the reference slab specimen, SM1, which has no fibers used in its concrete mixture. It is worth to mention that the slab specimen, SM6, which has the largest load-carrying capacity, also shows the highest ductility (172% enlargement in deflection when compared to the reference slab, SM1).